ANALISIS GRAMATIKA ALIH KODE DARI BAHASA INGGRIS KE BAHASA INDONESIA ATAU SEBALIKNYA - -, Margana (Diksi, 2009)
In Indonesia, switching from one language to another language is a commonphenomenon because Indonesian speakers are bilinguals. They use two or morelanguages, for example, Indonesian, English, or/and their own local language in a seriesof communication practices. With regard to the study of codeswitching, three perspectivescan be used. They include pragmatic, sociolinguistic, and linguistic analyses. Of the threeperspectives, analyzing codeswitching from a linguistic perspective seems to be interestingand challenging as the analysis gives an emphasis on the internal structure of thecodeswitching itself. This article deals with code switching from English to Indonesian orvice-versa analyzed from grammatical aspects as part of the linguistic analysis. It aims atreviewing the grammatical rules underlying the code-swictching.Keywords: code-switching, grammatical analysis